The Ophiuchus Disc Survey Employing Alma (Odisea)-Ii. the Effect of Stellar Multiplicity on Disc Properties - Perez-Marquez, S (Oxford University Press, 2020)
We present adaptive optics (AO) near-infrared (NIR) observations using VLT/NACO and Keck/NIRC2 of Ophiuchus DIsc Survey Employing ALMA (ODISEA) targets. ODISEA is an ALMA survey of the entire population of circumstellar discs in the Ophiuchus molecular cloud. From the whole sample of ODISEA, we select all the discs that are not already observed in the NIR with AO and that are observable with NACO or NIRC2. The NIR-ODISEA survey consists of 147 stars observed in NIR AO imaging for the first time, as well as revisiting almost all the binary systems of Ophiuchus present in the literature (20 out of 21). In total, we detect 20 new binary systems and one triple system. For each of them, we calculate the projected separation and position angle of the companion, as well as their NIR and millimetre flux ratios. From the NIR contrast, we derived the masses of the secondaries, finding that nine of them are in the substellar regime (30-50 MJup). Discs in multiple systems reach a maximum total dust mass of ∼50 M⊕, while discs in single stars can reach a dust mass of 200 M⊕. Discs with masses above 10 M⊕ are found only around binaries with projected separations larger than ∼110 au. The maximum disc size is also larger around single star than binaries. However, since most discs in Ophiuchus are very small and low-mass, the effect of visual binaries is relatively weak in the general disc population. © 2020 The Author(s).
Keywords: instrumentation: adaptive optics; planets and satellites: formation; protoplanetary discs; binaries: visual; submillimetre: planetary systems